Water-soluble malonic acid derivatives of C60 with a defined three-dimensional structure - Lamparth, Iris; Hirsch, Andreas (Journal of the Chemical Society - Series Chemical Communications, 1994)
Water-soluble malonic acid derivatives of C have been synthesised by hydrogenolysis of stereochemically defined mono-, bis- and tris-adducts of C and di(ethoxycarbonyl)methylene.